Effects of recombinant apolipoprotein A-I(Milano) on aortic atherosclerosis in apolipoprotein E-deficient mice. - Shah, P; Nilsson, J; Kaul, S; Fishbein, M; Ageland, H; Hamsten, A; Johansson, J; Karpe, F; Cercek, B (1998)
BACKGROUND: We previously reported marked inhibitory effects of recombinant apolipoprotein (apo) A-I(Milano)/phospholipid complex (A-I[Milano]/PC) on neointimal lesions in balloon-injured iliofemoral arteries of hypercholesterolemic rabbits. In this study, we tested the hypothesis that apo A-I(Milano)/PC would inhibit aortic atherosclerosis in apo E-deficient mice. METHODS AND RESULTS: Thirty-five apo E-deficient mice fed a high-cholesterol diet were included in the study. Control mice were killed at 20 (n=8) or 25 (n=7) weeks. Treated mice received 18 injections of either 40 mg/kg apo A-I(Milano)/PC (n=15) or PC only (n=5) intravenously every other day from 20 weeks until death at 25 weeks. Aortic atherosclerosis was identified with Sudan IV staining. Lipid and macrophage contents of the aortic sinus plaques were measured after oil-red O and Mac-1 antibody staining, respectively, and quantified with computed morphometry. In control mice, from 20 to 25 weeks, aortic atherosclerosis increased by 59% (11 +/- 1% versus 17 +/- 5% of the aortic surface, P=.002), and lipid content increased by 45% (22 +/- 8% versus 32 +/- 6% of plaque area, P=.02) without a significant change in macrophage content (10.8 +/- 2% versus 13.2 +/- 6%). Compared with 20-week-old untreated control mice, PC only-treated mice at 25 weeks demonstrated a 32% increase in aortic atherosclerosis (11 +/- 1% versus 15 +/- 4%, P=.01) and an increase in lipid content (22 +/- 8% versus 47 +/- 3%, P<.0001) without a change in macrophage content (10.8 +/- 2% versus 11 +/- 2%). In comparison with 20-week-old untreated control mice, 25-week-old apo A-I(Milano)/PC-treated mice demonstrated no increase in aortic atherosclerosis (11 +/- 1% versus 10 +/- 4%, P=NS), a 40% reduction in lipid content (22 +/- 8% versus 13 +/- 8%, P=.01), and a 46% reduction in macrophage content (10.8 +/- 2% versus 5.8 +/- 2.9%; P=.03). Serum cholesterol levels were markedly elevated in all groups and did not change significantly with apo A-I(Milano)/PC or PC only. In vitro, apo A-I(Milano)/PC stimulated cholesterol efflux from cholesterol-loaded FU5AH hepatoma cell lines in a dose-dependent manner, whereas PC only or PC-free apo A-I(Miano) had no effect. CONCLUSIONS: Recombinant A-I(Milano)/PC prevented progression of aortic atherosclerosis and reduced lipid and macrophage content of plaques in apo E-deficient mice despite severe hypercholesterolemia. Thus, A-I(Milano)/PC may have a role in inhibiting progression and promoting stabilization of atherosclerosis.